2017
DOI: 10.1016/j.jss.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane preconditioning protects from posttransplant injury in mouse lung transplantation

Abstract: We demonstrated that Sevo preconditioning has protective effects on lung transplants in both, PGD and AR. The observed amelioration may be attributed to suppressed inflammatory cytokines during PGD and the induction of alternatively activated macrophages during AR. These promising data could set the base for using Sevo preconditioning in donor lungs for a human trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Unfortunately, these results did not reach statistical significance. This is in accordance with previously reported findings that an attenuation of AR does not necessarily have an impact on the functionality of the transplanted organ on postoperative day 5 in this particular model [16]. However, the occurrence of AR has been linked to the development of chronic rejection, which is known to be one of the most important life-limiting factors after lung transplantation [3,23,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, these results did not reach statistical significance. This is in accordance with previously reported findings that an attenuation of AR does not necessarily have an impact on the functionality of the transplanted organ on postoperative day 5 in this particular model [16]. However, the occurrence of AR has been linked to the development of chronic rejection, which is known to be one of the most important life-limiting factors after lung transplantation [3,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…Naidu and colleagues previously demonstrated that TNF-α release from pulmonary macrophages 4 h after reperfusion might be critical for the development of lung I/R injury [15]. Therefore, the reduced plasma levels of TNF-α found in the ropivacaine animals 3 h after transplantation in the current study support the hypothesis that ropivacaine might be able to blunt I/R injury occurring during the process of transplantation and subsequently preserve endothelial barrier function [4,16,17].…”
Section: Discussionsupporting
confidence: 80%
“…LDH and TNF-α levels, however, showed no significant between-group difference. Various studies have shown that sevoflurane attenuates pulmonary IRI and inflammation [17][18][19][20]. In a rat EVLP model, Wang et al [21] showed that adding sevoflurane directly to the perfusion system upon the start of EVLP was associated with reduced levels of IRI injury markers like TNF-α and LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anesthetic agents, like sevoflurane, have been shown to reduce IRI in various organs [12][13][14][15][16], including the lungs [17][18][19][20][21], in animals and in humans. The use of sevoflurane may protect organs against IRI by preventing mitochondrial permeability transition pores from opening, preserving the glycocalyx, upregulating and stabilizing hypoxic inducible factors (HIFs) and directly affecting circulating immune cells [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%